2020
DOI: 10.3847/1538-4357/ab88d2
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Measure Hubble Parameter H(z) Using Fast Radio Bursts

Abstract: The Hubble parameter H(z) is directly related to the expansion of our universe. It can be used to study dark energy and constrain cosmology models. In this paper, we propose that H(z) can be measured using fast radio bursts (FRBs) with redshift measurements. We use dispersion measures contributed by the intergalactic medium, which is related to H(z), to measure the Hubble parameter. We find that 500 mocked FRBs with dispersion measures and redshift information can accurately measure Hubble parameters using Mon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 71 publications
0
32
0
Order By: Relevance
“…Furthermore, Li et al [196] show that the cosmic curvature of the universe, k, can also be model independently constrained to a precision of ∼0.076 using a set of lensed FRBs. Finally, it is also shown that a mock FRB sample of 500 FRBs with dispersion measures and redshift information can accurately measure Hubble parameter (with σH(z) = 0.06) using Monte Carlo simulation [199].…”
Section: Hubble Parametermentioning
confidence: 99%
“…Furthermore, Li et al [196] show that the cosmic curvature of the universe, k, can also be model independently constrained to a precision of ∼0.076 using a set of lensed FRBs. Finally, it is also shown that a mock FRB sample of 500 FRBs with dispersion measures and redshift information can accurately measure Hubble parameter (with σH(z) = 0.06) using Monte Carlo simulation [199].…”
Section: Hubble Parametermentioning
confidence: 99%
“…The deviation between the simulated value of H(z) and the theoretical one is about 6% at z = 2.4 (adapted from ref. [257]). microlensed.…”
Section: Hubble Parameter H(z)mentioning
confidence: 99%
“…Figure 10 (Color online) H(z) and 1σ errors derived from 500 mock FRBs are shown as blue dots. The red line represents the theoretical H(z) function.The deviation between the simulated value of H(z) and the theoretical one is about 6% at z = 2.4 (adapted from ref [257]…”
mentioning
confidence: 99%
“…Xu & Zhang proposed that FRBs can be used to probe the intergalactic turbulence [25]. Wu et al pointed out that FRBs can be used to measure the Hubble parameter H(z) independent of cosmological model [26]. Pagano & Fronenberg showed that the highly dispersed FRBs can be used to constraining the epoch of cosmic reionization [27].…”
Section: Introductionmentioning
confidence: 99%